IMPLIKASI â€œIN SEARCH OF EXELLENCEâ€ DI INDONESIA - Soegiono, Soegiono (potensio, 2014)
There are eight points of basis principle for deference result excellent from the big business in America in long time that in take side to evident act, always near with customers, having otonomy and entrepreneurship, increasing productivity pass through HRD, increasing value in main business, always in the business who known, employ a little staff in high level and high dedication. This analysis for tracing about â€œ in search of excellenceâ€ by Tom Peters in conection with business in Indonesia. This hypothesis very important to reciting in this analysis. There are conection in a manner evident interaction between America and Indonesia. Remembering that the both have the same system i.e. system open market and in market competitive structure.Key words : Implication â€œ in search of excellenceâ€ in Indonesia.